Effect of temperature on the removal of lead(II) by adsorption on China clay and wollastonite - Yadava K.P.; Tyagi B.S.; Singh V.N. (My University, 2025)
The removal of Pb(II) from aqueous solution by adsorption on china clay and wollastonite is an attractive process. The amount of Pb(II) removed by adsorption is highly dependent on the temperature of the adsorbate solution and favours low temperature. The equilibrium times were noted, i.e. 90 min for china clay and 120 min for wollastonite. The various rate parameters of the adsorption process have been determined at different temperatures. The activation energies were determined and found to be −5.345 kJ mol−1 and −8.730 kJ mol−1 for Pb(II)‐china clay and Pb(II)‐wollastonite systems, respectively. The adsorption isotherm was measured experimentally at various temperatures. The negative values of enthalpy change (ΔH = −77.95 kJ mol−1 and −16.40 kJ mol−1 for china clay and wollastonite, respectively) indicate the exothermic nature of the adsorption processes for both systems. The isosteric heats of the adsorption process have been determined at various surface coverages of the adsorbents used. The various thermodynamic parameters have been calculated to elucidate the mechanism involved in the adsorption process. Copyright © 1991 Society of Chemical Industry